Dynamics of metacognitive determinants of management activity in the process of professionalization - Karpov, A.V.; Karpov, А.А.; Karabuschenko, N.B.; Ivashchenko, A.V. (Èksperimentalʹnaâ psihologiâ, 2018)
The study is devoted to the research of identification of characteristics and patterns of development of metacognitive processes and personal qualities of management activity during professionalization. Hypothesis of the existence of a direct connection between the level of professionalization of the subject and the degree of coherence of the structural organization of the main metacognitive parameters was verified in this study. Using diagnostic and experimental techniques of the study of metacognitive processes and qualities (G. Shraw, R. Dennison, M. Grant, D. LaCosta, R. Dixon, S. Haltch, D. Everson, Z. Tobias), in combination with the author’s methods of structural-psychological analysis, in particular method for determining structural indices of the matrices of intercorrelations, we discovered and interpreted new features and regularities of dynamics of development of metacognitive processes and personality traits in the course of professionalization. It is revealed that professiogenetic restructuring of the parameters of the cognitive sphere are carried out simultaneously on two complementary levels (analytical and structural), and the most important transformations take place at the structural level. In the course of professionalization, the integrativity of basic metacognitive parameters significantly increases alongышву with reduction of their divergence (differentiation). We substantiates the position, according to which mechanisms of the integration plan and resulting synergistic effects, leading to expansion of cognitive and metacognitive potential of the subject, are the main tool of discovered transformations. Исследуется проблема, связанная с выявлением особенностей и закономерностей развития метакогнитивных процессов и качеств личности управленческой деятельности в ходе прфессионализации. Верифицируется гипотеза о существовании прямой связи между уровнем профессионализации субъекта и степенью когерентности структурной организации основных метакогнитивных параметров деятельности. Выборка испытуемых — 72 человека; 52 — мужского пола и 20 — женского; возраст — от 29 до 67 лет, русские. Использованы диагностические методики исследования метакогнитивных процессов и качеств (Г. Шроу, Р. Деннисон, М. Грант, Д. ЛаКоста, Р. Диксон, С. Халтч, Д. Эверсон, З. Тобиас) в сочетании с авторскими методиками структурно-психологического анализа, в частности, методом определения структурных индексов матриц интеркорреляций. Обнаружены и проинтерпретированы особенности и закономерности динамики развития метакогнитивных процессов и качеств личности в ходе профессионализации. Результаты исследования свидетельствуют о том, что профессиогенетические перестройки параметров метакогнитивной сферы осуществляются одновременно на двух взаимодополняющих уровнях — аналитическом и структурном. Показано, что наиболее значимыми являются трансформации, которые имеют место на структурном уровне. Их сущность состоит в том, что по мере профессионализации значимо возрастает интегрированность основных метакогнитивных параметров в сочетании со снижением их дивергентности и разнородности. Обосновано положение, согласно которому главным средством, лежащим в основе обнаруженных трансформаций, являются интегративные механизмы, формирующие синергетические эффекты и приводящие к расширению когнитивного и метакогнитивного потенциала субъекта.